DETECTION OF HABS IN THE COASTAL WATERS OF MAROS, SOUTH SULAWESI, INDONESIA - Rahmadi Tambaru, Arniati Massinai, Gustina (International Journal of Advanced Science and Technology, 2020)
The presence of harmful phytoplankton (HABs) can be caused by an increase in the fertility of water. This occurs because the waters get a nutrient supply from anthropogenic activities. The research aims to determine the abundance of harmful phytoplankton (HABs) in the Maros waters, South Sulawesi, Indonesia. The research employed one Way Anova and Principal Component Analysis. The results show that there are 22 genera of phytoplankton that have been detected, 4 genera include HABs, Ceratium, Dinophysis, Gymnodinium, and Protoperidinium. Based on its impact, HABs have a low proportion of which is about 2% when compared with the genus of phytoplankton, which is not HABs 98%. The oceanographic parameters show HABs cannot develop due to the concentration of nitrates and salinity as well as low temperatures, even though the brightness and orthophosphate are at high values.